A Biogeochemical Compromise: The High Methane Cost of Sequestering Carbon in Restored Wetlands. Issue 12 (23rd June 2018) - Hemes, Kyle S.; Chamberlain, Samuel D.; Eichelmann, Elke; Knox, Sara H.; Baldocchi, Dennis D.
Abstract: Peatland drainage is an important driver of global soil carbon loss and carbon dioxide (CO2 ) emissions. Restoration of peatlands by reflooding reverses CO2 losses at the cost of increased methane (CH4 ) emissions, presenting a biogeochemical compromise. While restoring peatlands is a potentially effective method for sequestering carbon, the terms of this compromise are not well constrained. Here we present 14 site years of continuous CH4 and CO2 ecosystem‐scale gas exchange over a network of restored freshwater wetlands in California, where long growing seasons, warm weather, and managed water tables result in some of the largest wetland ecosystem CH4 emissions recorded. These large CH4 emissions cause the wetlands to be strong greenhouse gas sources while sequestering carbon and building peat soil. The terms of this biogeochemical compromise, dictated by the ratio between carbon sequestration and CH4 emission, vary considerably across small spatial scales, despite nearly identical wetland climate, hydrology, and plant community compositions. Plain Language Summary: Wetlands play an important role in the climate system, with restoration commonly undertaken for the benefit of atmospheric carbon dioxide removal and carbon storage in the soil. While flooded conditions suppress carbon dioxide emissions from decomposition and sequester carbon, they also generate methane, another potent heat‐trapping greenhouse gas. Understanding the balance between these exchanges is important to our understanding of how restored or created wetlands will contribute to mitigating climate change. Here we present a long‐term record of continuous carbon dioxide and methane exchange from restored wetlands in Northern California to understand the ultimate climate impact of wetland restoration. Key Points: We report 14 site years of in situ ecosystem‐scale carbon dioxide and methane measurements over a range of restored wetlands in Northern California Large methane emissions caused the wetlands to be neutral to strong greenhouse gas sources while sequestering carbon and building peat soil Despite experiencing nearly identical meteorological conditions and similar species composition, methane and carbon sequestration scaled within, but not across, wetland sites